Impact of controlled particle size nanofillers on the mechanical properties of segmented polyurethane nanocomposites. (7th August 2007) - Finnigan, Bradley; Casey, Phil; Cookson, David; Halley, Peter; Jack, Kevin; Truss, Rowan; Martin, Darren
The impact of average layered silicate particle size on the mechanical properties of thermoplastic polyurethane (TPU) nanocomposites has been investigated. At fixed addition levels (3 wt% organosilicate), an increase in average particle size resulted in an increase in stiffness. Negligible stiffening was observed for the smallest particles (30 nm) due to reduced long-range intercalation and molecular confinement, as well as ineffective stress transfer from matrix to filler. At low strain (≤100%), an increase in filler particle size was associated with an increase in the rate of stress relaxation, tensile hysteresis, and permanent set. At high strain (1200%), two coexisting relaxation processes were observed. The rate of the slower (long-term) relaxation process, which is believed to primarily involve the hard segment rich structures, decreased on addition of particles with an average diameter of 200 nm or less. At high strain the tensile hysteresis was less sensitive to particle size, however the addition of particles with an average size of 200 nm or more caused a significant increase in permanent set. This was attributed to slippage of temporary bonds at the polymer-filler interface, and to the formation of voids at the sites of unaligned tactoids. Relative to the host TPU, the addition of particles with an average size of 30 nm caused a reduction in permanent set. This is a significant result because the addition of fillers to elastomers has long been associated with an increase in hysteresis and permanent set. At high strain, well dispersed and aligned layered silicates with relatively small interparticle distances and favourable surface interactions are capable of imparting a resistance to molecular slippage throughout the TPU matrix.